The Effects of Lockdowns on the Air Pollutants´ Concentration. Case Study of Nitra, Slovakia - BACULÁKOVÁ, Kristína; HARAKAĽOVÁ, Ľubica; KUCHARČÍK, Rudolf (Journal of Environmental Management and Tourism, 2021)
This study assessed the impact of lockdown on the air pollutants ‘concentration, namely NO 2 and PM 2.5 a PM 10 particles in the regional centre of Nitra city, Slovakia. For the purpose of the study, we compared the daily concentration of NO 2 and PM 2.5 and PM 10 particles during pre-, lockdown and post lockdown periods in 2020 and compared with daily concentrations in 2019 with the respect to the meteorological parameters that may potentially affect these values. The results of the study suggest that the decrease in concentrations of harmful particles was not significant, on the contrary, in some periods of 2020 they increased. Only the decrease in the concentration of NO 2 was statistically significant, which is in line with the studies carried out so far in the world.